High‐Resolution Observation of Nucleation and Growth Behavior of Nanomaterials Using a Graphene Template. (29th January 2014) - Jo, Janghyun; Yoo, Hyobin; Park, Suk‐In; Park, Jun Beom; Yoon, Sangmoon; Kim, Miyoung; Yi, Gyu‐Chul
<x xml:space="preserve">Abstract</x> By using graphene as an electron beam‐transparent substrate for both nanomaterial growth and transmission electron microscopy (TEM) measurements, we investigate initial growth behavior of nanomaterials. The direct growth and imaging method using graphene facilitate atomic‐resolution imaging of nanomaterials at the very early stage of growth. This enables the observation of the transition in crystal structure of ZnO nuclei and the formation of various defects during nanomaterial growth. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>